A Brief History of the Middle East - Catherwood, Christopher (London Robinson, 2011)
Offers a history of the Middle East, and explains the connection between some of today's international crises and events that originated in the region.
Include Index and Bibliography
Keywords: Middle East -- Manners and customs -- Politics and government